Effect of Low-level Visual Details in Perception of Deformation - Han, D.; Keyser, J. (Computer graphics forum, 2016)
We quantitatively measure how different low‐level visual details can influence people's perceived stiffness of a deformable sphere under physically based simulation. The result can be used to create a metric for artists in designing textures to enhance or reduce the stiffness perceived by a viewer. We use a checkerboard texture to render the simulation of a free falling sphere that collides with the ground and bounces up. We vary the spatial frequency and contrast of the checkerboard pattern according to results seen in a previous study on the Spatial‐Temporal Contrast Sensitivity Function (CSF). We find that checkerboard pattern with certain combinations of spatial frequency and contrast can reduce the perceived stiffness. We also add a high contrast checkerboard background to study how complex backgrounds can influence the effect of low‐level details in textures of foreground objects. Our study shows that the effect of low‐level visual details in foreground objects observed previously disappears in this situation. This indicates the importance of background, even if it is static.